GE_GERICHTE P/19977/2009 vom 16. Oktober 2013 - GE Cour de justice (2013)
IN DUBIO PRO REO; VOIES DE FAIT; MENACE(DROIT PÉNAL); ATTÉNUATION DE LA PEINE; EXEMPTION DE PEINE | CP.180; CP.126; CPP.399.3; CP.48.c; CP.54